Domestikasi Tanaman Jombang (Taraxacum Officinale) Melalui Perlakuan Zat Pengatur Tumbuh Untuk Memperoleh Benih Berkualitas Baik - Addelia Shakilla; Siti Asmaniyah Mardiyani; Maria Ulfah (Universitas Islam Malang, 2021)
Jombang plant (Taraxacum officinale) is a wild plant that is commonly found in the surrounding land, but there are still many people who do not know about the existence and efficacy of this plant. This study aims to determine the effect of the administration of growth regulators ethrel and gibberellins on the growth and quality of jombang (Taraxacum officinale) seeds. The research was conducted in the Green House of the Faculty of Agriculture, Islamic University of Malang, the analysis of the seed test was carried out in the physiology laboratory of the Faculty of Agriculture, Islamic University of Malang. The study consisted of 6 combination treatments of Ethrel and GA3 hormones with 1 control treatment. Observational data were analyzed using the F test at 5% level (ANOVA) and the BNJ test at 5% level. The results showed that treatment E1 (ethrel 100 ppm) was the treatment with the highest average value on the variable plant height difference. Treatment G2 (GA3 100 ppm) gave better results on the variable amount difference. Treatment E2 (ethrel 200 ppm) gave the best results on the variable seed weight in flowers per floret. The control seed quality variable gave the best results on the variable germination and germination speed.